2024
DOI: 10.3390/plants13020155
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Approach to Selected Species of Tanacetum L. (Asteraceae): Insights into Morphology and Phytochemistry

Claudia Giuliani,
Martina Bottoni,
Fabrizia Milani
et al.

Abstract: In this work, we studied Tanacetum vulgare, Tanacetum parthenium, and Tanacetum corymbosum (Asteraceae) cultivated at the Ghirardi Botanic Garden (Toscolano Maderno, Brescia, Northern Italy) of the University of Milan. An integrative research approach was adopted: microscopic and histochemical, with special focus on the secretory structures responsible for the productivity of secondary metabolites; phytochemical, with the analysis of the essential oil (EO) profiles from the air-dried, flowered aerial parts col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
1
4
2
Order By: Relevance
“…The present study supports these data, and the RM sample afforded an even higher camphene amount (16.12%). On the contrary, this substance was lacking in EO from T. parthenium cultivated in Northern Italy [183]. Unlike previous results, Giuliani et al also reported a large content of farnesol (28.83%) belonging to the oxygenated sesquiterpenes [183], which were completely absent in this investigation.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…The present study supports these data, and the RM sample afforded an even higher camphene amount (16.12%). On the contrary, this substance was lacking in EO from T. parthenium cultivated in Northern Italy [183]. Unlike previous results, Giuliani et al also reported a large content of farnesol (28.83%) belonging to the oxygenated sesquiterpenes [183], which were completely absent in this investigation.…”
Section: Discussioncontrasting
confidence: 94%
“…Camphor has been recognised as the main compound identified in feverfew EOs from various locations, including Turkey, Egypt, Iran, Serbia, Italy, and Tajikistan. Typically, its content is around 45-65% [6,[25][26][27][28]30,131,[180][181][182][183], which is in agreement with our results. Sharopov et al detected a concentration of up to 94% in EO from a wild population growing in Tajikistan [34].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The widespread distribution of T. vulgare may be a ributed to several factors, including its wide range of climatic adaptability and phenotypic plasticity, great self-seeding potential, ripening of numerous seeds, vegetative reproduction via rhizomes, etc. [27][28][29][30]. Additionally, successful tansy outspreading can be explained by its allelochemicals, which have an impact on the germination of seeds, the development of roots and the overall vegetation of surrounding plants, mainly caused by insufficient mineral and water intake, damage to cell membranes, imbalance of phytohormones, disruption of the photosynthesis process, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The term allelopathy was first used by Austrian scientist H. Molisch in 1937, when he published the results of research concerning the action of ethylene upon some plants [32]. Allelopathy is the phenomenon whereby organisms (mainly plants) liberate specific metabolites, known as allelochemicals into the environment that have an affect (positively or negatively) on the vegetation of other surrounding plants and all biological systems [30]. Allelochemicals are mainly primary and secondary metabolites, generally water-soluble chemicals belonging to a wide range of compound classes, such as amino and phenolic acids, terpenoids, alkaloids, flavonoids, anthocyanins, lignins, glucosinolates, tannins, etc.…”
Section: Introductionmentioning
confidence: 99%